2014
DOI: 10.1177/1049909114530492
|View full text |Cite
|
Sign up to set email alerts
|

End-of-Life Issues in UK Medical Schools

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 16 publications
1
20
2
Order By: Relevance
“…A 2000 study found PC teaching was offered as a separate course in 13% of medical schools, compared to 20% in a 2013 survey. 6,14 In 2000, PC was covered in 'only 1 or 2 lectures' in 13% of schools (10% in 2013), as module of a larger course in 25% of schools in 200 (26% in 2013) and 'integrated throughout the curriculum' in 50% in both periods. 6,14 Incorporation of PC into the curriculum involves 'a complex process of individual, institutional, clinical, patient and curricular factors'.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2000 study found PC teaching was offered as a separate course in 13% of medical schools, compared to 20% in a 2013 survey. 6,14 In 2000, PC was covered in 'only 1 or 2 lectures' in 13% of schools (10% in 2013), as module of a larger course in 25% of schools in 200 (26% in 2013) and 'integrated throughout the curriculum' in 50% in both periods. 6,14 Incorporation of PC into the curriculum involves 'a complex process of individual, institutional, clinical, patient and curricular factors'.…”
Section: Discussionmentioning
confidence: 99%
“…6,14 In 2000, PC was covered in 'only 1 or 2 lectures' in 13% of schools (10% in 2013), as module of a larger course in 25% of schools in 200 (26% in 2013) and 'integrated throughout the curriculum' in 50% in both periods. 6,14 Incorporation of PC into the curriculum involves 'a complex process of individual, institutional, clinical, patient and curricular factors'. 13 This study demonstrates considerable variation in the development and organisation of PC education across UK medical schools, with limited leadership, course review, titular recognition of educators and resource allocation in some institutions, especially those without academic PC departments.…”
Section: Discussionmentioning
confidence: 99%
“…9 The majority of US medical schools now offer this option for which 90% of students are involved. Studies have shown 17,18 that introducing medical personnel to palliative care, particularly hospice, helps to protect the patient from ineffective interventions near the end of life and assists the patient and family in making educated decisions regarding treatment options.…”
Section: Hospice Involvementmentioning
confidence: 99%
“…The number of teaching hours, however, has not changed significantly in the 21st Century (average number in 2015 was 13; United Kingdom averaged 27 hours). 9 An interdisciplinary team effort has increased, as the trend in offerings and the professional background of the ''team'' has varied over time, with physicians continuing as the key players. A meta-analysis of EOL studies 10 presented evidence of the training experience of residents revealing that a multidisciplinary approach improved confidence and overall EOL care and also helped students to cope with death experiences.…”
Section: End-of-life Offerings Over Timementioning
confidence: 99%
See 1 more Smart Citation